MEMPERKUAT PRODUKTIVITAS: PERAN KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA PADA PT. NAGA SEMUT KEBUMEN - Ignatius Soni Kurniawan; M Hamdan (Universitas Muhammadiyah Metro Lampung, 2021)
Employees who have high productivity are company assets, thus understanding the causes of productivity is a way to increase it. This study examines the influence of transformational leadership, motivation, and the work environment partially on employee work productivity. The study used a population of employees of PT. Naga Semut Kebumen with 60 respondents. Data were collected through a survey with a closed questionnaire instrument and then analyzed by multiple linear regression. The findings imply that organizations need to provide more opportunities for individuals with transformational styles to lead in order to encourage the productivity of manufacturing workers. The majority of workers are women, so providing a conducive manufacturing work environment is the most influential factor supporting productivity.Keywords: Transformational Leadership, Motivation, Work Environment, Work Productivity